ANALISIS SPASIAL LAHAN KRITIS DI KECAMATAN BUKAL KABUPATEN BUOL - Arif, Nursida (AKADEMIKA, 2013)
Land conversion on the increase due to the insistence of the human need for natural resources available. The impact of this is the emergence of critical land that become a new problem for the government. Spatial analysis of critical land is done to see the spread of critical land with the aim of helping to prioritize conservation or rehabilitation of land in the study area. Sampling was is done with field survey and analysis of the maps consisting of variables that determine critical land. The parameters are used as a determinant of critical class of land i.e land cover, slope, solum depth, and soil texture. The results show areas of research are somewhat critical areas and critical potential spread of plantation area while critical in most residential areas. The dominant factor affecting the critical of land in the district, namely Buccal slope and land conversion.